Generation Z and Halal Travel: How Digital Promotion and Service Quality Influence Interest - Syamsurizal, Syamsurizal; Andrini, Rozi; Rismawati, Viona (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2024)
One of the industries that has the potential to expand in Indonesia in recent years is halal tourism. Therefore, tourist destination managers must improve management, including digital promotions and services. Especially for Generation Z who are the largest number of tourists on halal tourism. The study aims how digital promotion and service quality influence interest of Gen Z. Quantitative approach with multiple linear regression analysis is the method used in this study. Digital promotion and service quality influenced the interest of Gen Z tourists to travel for halal tourims. Another finding is that digital promotion and service quality of Tan Kayo Sharia Eco Park are in accordance with Islamic principles and Minang culture, which is very strong with Islamic nuances. This research should be a reference for decision-making on digital promotion and services of halal tourist destinations, which will encourage the improvement of local to national sharia economies.